From Sacred Space to Religious Tourism: The Transformation of the Thousand Doors Mosque Tangerang, Indonesia - Merina, Merina; Pratama, Cahya Adhitya (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2025)
The transformation of the Thousand Doors Mosque (Masjid Seribu Pintu) in Tangerang reflects a shift in function from a place of worship to a multifunctional space encompassing religious, social, cultural, and economic dimensions. This study aims to examine the historical and cultural factors driving this transformation, the mosque's role in religious tourism, and its impact on the local community. Using a qualitative approach, data were collected through field observations, in-depth interviews with mosque administrators and visitors, and a review of relevant literature. The findings reveal that the mosque’s unique architectural elements—such as its numerous doors, dark corridors, Islamic calligraphy, and tawasul chamber—not only enhance the spiritual experience but also serve as key attractions for religious tourists. This transformation is supported by active local community participation in economic activities and the preservation of spiritual values, although it poses challenges in maintaining the sanctity of worship. These findings suggest the need for sustainable religious tourism policies that balance the mosque’s sacred function with its socio-economic role. The originality of this research lies in its integration of religious architecture, Islam Nusantara spirituality, and cultural capital within the context of contemporary tourism. This study contributes conceptually to scholarship on sacred space, religious tourism governance, and the mosque’s role as a cultural and economic hub in modern Muslim societies.